FIGURE 8 in Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata) - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
FIGURE 8. Rhamphostomella pacifica (O'Donoghue, 1925). Neotype, ZIRAS 1/50124 (Kronotsky Gulf, eastern Kamchatka, Pacific Ocean). A. Colony margin with developing zooids. B. Zooids and two vicarious avicularia near colony margin. C. Orifice with suboral avicularium. D. Lateral view of zooids in young part of colony, showing communication slits (sites of the future ooecial development), developing ooecium and position of suboral avicularium. E. Young autozooids, with communication slits (arrows) around which distal zooids will develop ooecia. F. Ovicellate zooids with suboral and adventitious avicularia in older part of colony. G. Ovicellate zooids, showing variation in size and position of adventitious avicularia. H. Oblique view of two ovicellate zooids in older part of colony, with ooecia covered by the secondary calcification. I. Interior of frontal shield, showing ring scar and areolae. J. Internal view of primary orifice. K. Basal colony surface, showing irregular protuberances. L. Frontal shield interior, showing ring scar and exterior wall microstructure of umbonuloid component. M. Lateral view of bilaminate part of colony, showing ooecia partially covered by secondary calcification and lateral walls with mural pore chambers. Scale bars: A, G, K, 500 μm; B, D–F, 250 μm; C, I, J, 100 μm; H, M, 200 μm; L, 50 μm. Published as part of Grischenko, Andrei V., Gordon, Dennis P., Taylor, Paul D., Kuklinski, Piotr, Denisenko, Nina V., Spencer-Jones, Mary E. & Ostrovsky, Andrew N., 2022, Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata), pp. 1-115 in Zootaxa 5131 (1) on page 34, DOI:10.11646/zootaxa.5131.1.1, http://zenodo.org/record/6521113